A descriptive analysis of spontaneous reports of antipsychotic‐induced tardive dyskinesia and other extrapyramidal symptoms in the Japanese Adverse Drug Event Report database - Yosuke Saga; Chih‐Lin Chiang; Akihide Wakamatsu (Wiley, 2024)
Abstract AimThe aim of this study is to summarize the spontaneous reports of tardive dyskinesia (TD) and extrapyramidal symptoms (EPSs) that occurred in Japan over the past decade. MethodsThe study analyzed TD and EPS cases reported in the Japanese Adverse Drug Event Report database between April 2011 and March 2021. The cases were stratified by the diagnoses of schizophrenia, bipolar disorders, and depressive disorders. ResultsIn total, 800 patients including a total of 171 TD cases and 682 EPS cases were reported in the JADER database across psychiatric diagnosis. The cases were caused by first‐generation antipsychotics (FGA, TD: n = 105, EPS: n = 245) and second‐generation antipsychotics (SGA, TD: n = 144, EPS: n = 598). The SGA were categorized based on Neuroscience‐based Nomenclature (NbN) regarding pharmacological domain and mode of action, which were reported evenly as the offending agents. Among reported treatment and outcome in TD cases (n = 67, 37.6%) and EPS cases (n = 405, 59.3%), the relatively limited number of TD cases were reported as recovered/improved was also limited (n = 32, 47.8%) compared to those of EPS cases (n = 266, 65.7%). Some cases still had residual symptoms or did not recover fully (TD: n = 21, 31.3%, EPS: n = 77, 19.0%). Conclusion Tardive dyskinesia and EPS have been widely reported in Japan over the past decade across psychiatric diagnoses and antipsychotic classes. Limitations It is important to acknowledge the presence of reporting bias and the lack of comparators to accurately assess risks. Owing to the nature of spontaneous reporting, the estimation of prevalence is not feasible.